Analisis Beberapa Faktor Yang Mempengaruhi Kinerja Karyawan Pt.Bank Central Asia, Tbk (BCA) KCU Solo Slamet Riyadi - Puspajati, Raden Rara Intan; , Drs. Kusdiyanto, S.E., M.Si (2016)
The aim of this study was to determine some of the factors affecting the performance of employees at PT.Bank Central Asia, Tbk (Bca) KCU Solo Slamet Riyadi in terms of the factors that influence it, namely work motivation, ability to work, and work environment. Tests were performed in this study using a test instrument that research validity and reliability test, test the classical assumption of normalistas test, test the hypothesis that multiple linear regression, t test, F test and coefficient of determination or R2. The data in this study are primary data obtained by distributing questionnaires to the respondents (PT.Bank Central Asia, Tbk (Bca) employees KCU Solo Slamet Riyadi), samples taken are as many as 50 employees. Based on the results of the study showed that the ability to work variable is a variable that has a dominant influence on employee performance in PT.Bank Central Asia, Tbk (Bca) KCU Solo Slamet Riyadi. T test evidenced in work motivation and ability to work has a significant influence on employee performance, because the statistical t-test (t) is greater than the value t table (2,379> 2,012) and (3,239> 2,012). While missing for environment variables have a significant influence on employee performance, because the statistical t-test (t) is smaller than the value ttable (1.346 <2.012). The results of the F test showed that there is a simultaneous and significant influence between work motivation, ability to work and the work environment on employee performance, because the F-test statistic (F count) is greater than the value of F table (22.013> 3.23) with probability less than 0.05 (0.000 <0.05) The results obtained coefficient of determination or R2 of 0.589, meaning 58.9% of the variation changes the performance of the employee fluctuation due to changes in work motivation, ability to work, and work environment. While the remaining 41.1% were caused by other factors not analyzed in the model used in the study. Keywords: Work Motivation, Job Skills, Work Environment, Employee Performance.